Synthesis of Methacrylate-Based Functional Monomers via Boron Ester Acidolysis and Their Polymerization - Gunes, Deniz; Karagoz, Bunyamin; Bicak, Niyazi (Informa UK Limited, 2009)
A new method is presented for the synthesis of functional methacrylate ester monomers. In this method, boron esters of appropriate alcohols were reacted with methacrylic acid to give the corresponding methacrylic ester monomers. The monomers N,N-dimethylaminoethyl methacrylate (DAMA), 2-chloroethyl methacrylate (CEMA), 2-bromoethyl methacrylate (BEMA), 2-methoxyethyl methacrylate (MEMA) and butyl methacrylate (BMA) were prepared in a laboratory scale by a two-step one-pot process. In the first step, the corresponding boron esters were formed by azeotropic removal of water. Subsequently, addition of methacrylic acid and heating at 140–160°C in the presence of pyridine resulted in acidolysis of the boron esters, yielding the functional methacrylate ester monomers in acceptable yields (41–71%). The monomers obtained were characterized by 1H-NMR and FT-IR spectra after isolation and purification. Their polymerizability was also demonstrated.